TOC, TOC/TN, δ13Corg and a new chronologic framework of core SG06 from Lake Suigetsu (Japan) since 146 ka - Alexander Francke; Jonathan James Tyler; Richard A Staff; Danielle McLean; Vanessa Nowinski; Megumi Saito-Kato; John Tibby; Minoru Ikehara; Yusuke Yokoyama; Katsuya Gotanda; Tsuyoshi Haraguchi; Takeshi Nakagawa; et al. (PANGAEA, 2025)
We present new palaeoclimate data from Lake Suigetsu (Japan) core SG06 including total organic carbon (TOC), total nitrogen (TN), TOC/TN ratios, carbon isotope analyses of organic carbon (δ13Corg) and Cryptomeria pollen abundance back to the penultimate glacial period (146 ka). The data is used to reconstruct orbital-scale monsoon dynamics in Japan. The sediments down to a maximum penetration depth of 73m were recovered in summer 2006 using a hydro-pressure thin-walled piston sampler and a floating platform by the Suigetsu 2006 Project Members. A new chronology for the Lake Suigetsu extquotesingles sediments were developed beyond the well-constrained radiocarbon limit based on (1) tephrochronology, and (2) tephrostratigraphy, and (3) careful alignment of Cryptomeria pollen abundance between Lake Suigetsu and marine core MD01-2421 located in the northern Pacific Ocean.